Cis-1, 2-Bis(diphenylphosphino)ethylene copper(i) catalyzed C–H activation and carboxylation of terminal alkynes. (25th October 2017) - Trivedi, Manoj; Smreker, Jacob R.; Singh, Gurmeet; Kumar, Abhinav; Rath, Nigam P.
Abstract : Reaction of CuX (X = CN, SCN) and cis -1, 2-bis(diphenylphosphino)ethylene (dppet) in 1 : 1 molar ratio in DCM–MeOH (50 : 50 V/V) afforded copper(i ) complexes. These complexes were shown to be efficient catalysts in comparison to CuCN/CuSCN for the conversion of terminal alkynes into propiolic acids with CO2 at room temperature. Abstract : The reaction of cis -1, 2-bis(diphenylphosphino)ethylene (dppet) with CuX (X = CN, SCN) in 1 : 1 M molar ratio in DCM–MeOH (50 : 50 V/V) under refluxing conditions gave two dimeric Cu(i ) complexes, viz. [Cu2 (μ-CN)2 (κ 2 - P, P -dppet)2 ] (1 ) and [Cu2 (μ2 -SCN)2 (κ 2 - P, P -dppet)2 ] (2 ). These complexes have been characterized by elemental analyses, IR, 1 H and 31 P NMR, and electronic absorption spectroscopies, and ESI-MS. The molecular structure of2 was confirmed by single crystal X-ray diffraction, which indicated that2 exists as a centrosymmetric dimer in which the two copper centers are bonded to two dppet ligands and two bridging thiocyanate groups in a μ2 -manner. The electrochemical properties of1 and2 were studied by cyclic voltammetry. Both the complexes exhibited strong luminescence properties in the solution state at ambient temperature. Both the complexes were found to be efficient catalysts for the conversion of terminal alkynes into propiolic acids with CO2 . Owing to their excellent catalytic activity, the reactions proceed at atmospheric pressure and ambient temperature (25 °C). The catalytic products were obtained in excellent yields (90–97%) by using the complex loading of 1 mol%.